2015
DOI: 10.1016/j.cell.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

PTX3 Is an Extrinsic Oncosuppressor Regulating Complement-Dependent Inflammation in Cancer

Abstract: A commentary on PTX3 is an extrinsic oncosuppressor regulating complement-dependent inflammation in cancer by Bonavita E, Gentile S, Rubino M, Maina V, Papait R, Kunderfranco P, et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
368
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 351 publications
(385 citation statements)
references
References 57 publications
11
368
3
3
Order By: Relevance
“…In contrast to C5aR, which has been reported to act via induction of MDSC and inhibition of CD8 + CTL responses (6), we show that C3aR deficiency/antagonism leads to a reduction in tumor-associated macrophages, along with increased neutrophil and CD4 + T cell populations. Macrophages are an essential component of tumor-promoting inflammation, and reduced tumor growth in C3-deficient mice has recently been associated with a reduction in tumor-associated macrophages (25). However, this same group showed that the reduction in macrophages was not sufficient to completely ablate tumor susceptibility, suggesting the involvement of other cells or mechanisms.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to C5aR, which has been reported to act via induction of MDSC and inhibition of CD8 + CTL responses (6), we show that C3aR deficiency/antagonism leads to a reduction in tumor-associated macrophages, along with increased neutrophil and CD4 + T cell populations. Macrophages are an essential component of tumor-promoting inflammation, and reduced tumor growth in C3-deficient mice has recently been associated with a reduction in tumor-associated macrophages (25). However, this same group showed that the reduction in macrophages was not sufficient to completely ablate tumor susceptibility, suggesting the involvement of other cells or mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…Complement is now thought to be a key component of cancer-related inflammation, and a recent study has suggested that exacerbated inflammation in the tumor microenvironment promotes genetic instability (25). The canonical proinflammatory mediator C5a has been widely implicated for a role in tumor growth, with both tumor-promoting and tumor-inhibitory effects reported, depending on tumor type, immune status of the host, and C5a levels (6)(7)(8)(9)26).…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that complement promotes growth and expansion of malignant tumors. Bonavita et al showed that complement promotes malignant transformation of cells exposed to chronic inflammation induced by chemical carcinogens (39). However, additional studies are required to dissect the effect of early versus late stages of complement activation on various stages of oncogenesis.…”
Section: Complement and Cancermentioning
confidence: 99%
“…Colon tumor cell secretion of the C-C family chemokine, CCL2, was essential for tumorigenesis through recruitment and activation of protumorigenic myeloid cells (40). Pentraxin 3 (PTX3) is a tumor suppressor that activates complement-mediated antitumor immunity and is epigenetically silenced due to methylation in colon tumors (41) …”
Section: Hypoxia and Epithelial-elicited Tumor Inflammatory Responsementioning
confidence: 99%